PENDAMPINGAN MASYARAKAT DESA JANAPRIA DALAM PEMBUATAN PUPUK ORGANIK DAN DEKOMPOSER BERBAHAN LIMBAH KOTORAN SAPI - Fahruddin; Irham, Muhammad; Lupita, Nia; Noviana, Renanda; Putrabinawan, Diega Armanda; Fitri; Rahman, Fazrul; Syaaran, Adzim; Anggini, Baiq Puspita Ayu; Pradita, Yolanda Eriana; S, Ferica Ramdani; Khotimah, Sabti Hajjatul (Jurnal Wicara, 2024)
Kuliah Kerja Nyata (KKN) are a form of student activity that involves going directly into the community to apply the knowledge gained in college to help solve problems and empower local communities. The KKN activities carried out in Janapria Village, Janapria District, Central Lombok Regency, by Mataram University students certainly consist of various activities with the main target being the utilization and development of village potential. The aim of implementing this KKN activity is to help the community develop the potential of underdeveloped villages, one of which is the use of cow dung waste into organic fertilizer and decomposer. There are 5 methods used in this activity, namely: (1) Survey and mapping method (2) Social approach method, (3) Participatory method, (4) Mentoring method, and (6) Evaluation method. The output of this activity is a product in the form of organic fertilizer and decomposer. The people of Janapria Village, especially farmers and livestock breeders, have the awareness to utilize the local potential of the village, namely livestock manure into something of economic value. Thus, this activity was generally successful in increasing the understanding and participation of the Janapria Village community in using livestock waste wisely for the sake of agricultural sustainability and a sense of caring for the environment.